RAINFALL VARIABILITY AND RICE PRODUCTIVITY OVER KERALA - Gopika, S; Lekshmi Mudra, B; Chaidanya, K. and Varsha, K.M (Journal of Aquatic Biology and Fisheries, 2014)
An attempt was made to study the trend in rice area under cultivation, production and productivity in Kerala to f ind out relationship between rainfall variability and rice yield. The average rainfall during the kharif is 2061.8mm while 563.3mm during rabi. Rainfall trend in kharif seasons showed a declining trend while rabi season indicated an increasing trend during the study period. The area under rice and rice production were in decline. It revealed that high rainfall during September and October are not conducive as it intervenes with harvest during kharif and transplanting during rabi.